FRIENDLY ENGLISH INSTRUCTION FOR DYSLEXIC LEARNERS - Khafidhoh Khafidhoh (Universitas Ahmad Dahlan)
It is not really an easy work to get the general acceptance of dyslexia among the parents, teachers, society, government, and so on. However, in this era, we can see a number of countries actively fight for the dyslexics’ rights in life, education, job, etc. In Indonesia, Indonesian Dyslexia Association has run several activities to support people with dyslexia. In short, Indonesian people start to realize the importance of having the right exposures on dyslexia and taking part to support the dyslexics. However, the partial understanding about dyslexia and the related things can cause the inappropriate and unfriendly actions to support them. Thus, in this article, the writer tries to discuss about the way how to create friendly English instruction for dyslexic learners which is based on the experts’ suggestions. In accordance with the topic, this article covers the descriptive and critical review on dyslexic learners, English instruction for dyslexic learners, and friendly English instruction for dyslexic learners. Finally, this article is expected to give the brief information to both of the general readers and the professionals. In general, it is expected to be the guidance to solve the problems on dyslexia, especially related to the English instruction. Then, it is also expected to be used as one of the references to discuss and conduct the related topics and researches.